Lost in the Yellowstone : Truman Everts's thirty-seven days of peril - Everts, Truman, 1816-1901 (University of Utah Press, 1995)
"In September 1870, Truman Everts was separated from one of the first exploratory parties in what is now Yellowstone National Park. With little food, equipment, or cold-weather clothing Everts spent more than a month wandering the wilderness before two mountaineers found him alive: frostbitten, scalded, and delirious. Nobody else has been lost so long in Yellowstone and survived." "This is one of the West's most fantastic dramas, high adventure in every sense of the word." "Lost in the Yellowstone contains Truman Everts's original high-adventure chronicle of hardship and survival, newly augmented with biographical and background information."--Jacket